Elevation-dependent decline in vegetation greening rate driven by increasing dryness based on three satellite NDVI datasets on the Tibetan Plateau. (December 2019) - Liu, Laibao; Wang, Yang; Wang, Zheng; Li, Delong; Zhang, Yatong; Qin, Dahe; Li, Shuangcheng
Graphical abstract: Highlights: Large discrepancies exist in the satellite-derived NDVI datasets during 2000–2012. Rising temperature drives the regional vegetation greening on the Tibetan Plateau. As elevation rises, vegetation greening rate is in contrast to the warming rate. Increasing dryness drives elevation-dependent decline in vegetation greening rate. Abstract: In northern high-latitude regions, amplified vegetation greening has been observed due to a larger warming rate than the rate at low latitudes. Similarly, on the Tibetan Plateau (TP), the warming rate is larger at high elevation than that at low elevation. Our results show that large discrepancies exist in the trends in the satellite-derived Normalized Difference Vegetation Index (NDVI) during 2000–2012, indicating the importance of using three satellite-derived NDVI datasets (Global Inventory Modeling and Mapping Studies, Moderate Resolution Imaging Spectroradiometer and SPOT) in the evaluation of vegetation activity on the TP. Based on three NDVI datasets, during 2000–2012, rising temperature drove the regional vegetation greening across the TP, but the vegetation greening rate contrasted with that of elevation-dependent warming. Here, with simultaneous use of climate observation data, we found that declining water availability with rising elevation may restrict and offset the positive effect of rising temperature on vegetation greening, resulting in the declining rate of vegetation greening as elevation increases on the TP. Our results highlight the significant influence of precipitation on elevation-dependent changes in vegetation activity in rapidly warming mountain ecosystems.